PENGARUH KURIKULUM MERDEKA TERHADAP PRESTASI BELAJAR SISWA - Nurhikmawati; Sandi; Azis, Emmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Merdeka curriculum on student achievement. The research method used is quantitative. The data processed is questionnaire data. The data collection methods used in this study were questionnaires and interviews, where the author conducted direct interviews regarding the implementation of the Merdeka curriculum. Based on the data analysis conducted, it was found that the Merdeka curriculum had a positive and significant impact on student achievement in class XI Hospitality at SMKN 7 Bone. This is evidenced by the results of a simple regression analysis explaining Y = 9.382 + 0.621X, which determines that for every 1 score in variable X (Merdeka Curriculum), variable Y (Student Achievement) will increase student achievement by 0.621. Furthermore, the t-test results show that the calculated t-value is greater than the t-table, namely 2.919 > 1.717 with an n of 22, equivalent to a significant value of 0.008 < 0.05, using statistical significance.